Motivation And Attitude of International Students Towards Learning Hungarian - Khelifa, Alaeddine; Batyi, Szilvia (Universitas Jambi, Indonesia, 2023)
In second/foreign language learning, motivation, anxiety, and attitude play a role (Pham, 2021). Dörnyei (2001) pointed out that the classroom is such a complex place that a single motivational principle cannot explain what happens within because motivation is a complex, composite entity with distinct and state-like context-specific components. Additionally, anxiety and attitude are complex constructs, and despite the differences in research methods used and the conceptualization of various motivational configurations, the general view among these studies is to treat motivation, anxiety, and attitude as dependent constructs characterized by multiple guiding variables (Dörnyei, 2010; Galánta, 2009; MacIntyre et al., 2015). Current approaches have also called for integration between these constructs and language learning situations in the FL classroom. These multi-variable approaches help this research explores motivation, anxiety, and attitude in 280 international students in Hungary taking courses in L2 Hungarian with a 34-item questionnaire. As expected, motivation, anxiety, and attitude are strongly related, and the self-guides emerge as strong predictors of motivated behavior and attitudes and have a negative correlation with language anxiety (Csizér & Dörnyei, 2005). Anxiety integrates with self-confidence, and language proficiency has the highest correlation with attitude. Finally, the attitude toward the course correlates highly with the attitude toward the community. Learners who report high ideal selves are thus most likely linguistically self-confident and exhibit a motivated behavior that encourages them to be exposed to Hungarian outside their classrooms and to have a positive attitude toward the community, the Hungarian language, and their teachers.